Elements in political science - Bealey, Frank; Chapman, Richard A.; Sheehan, Michael (Michael J.) (Edinburgh : Edinburgh University Press, 1999)
This introductory textbook provides the ideal basis for students coming to Politics for the first time. The book opens with thequestion 'What is Politics?' and then explores the four major 'elements' : Comparative Institutions, Political Ideologies, Public Administration and International Relations. The book has been divided into five easy-to-use sections, each with a guide to literature for further study. Each chapter ends with two essay questions, making this an ideal teaching and revision tool. Key features -- Covers the core elements of a Political Science undergraduate degree -- Ideal for revision of the subject: includes 50 essay questions -- Offers helpful guides to the literature in each area. Written by a distinguished team of authors with many years of teaching experience. -- Provided by publisher
Preface -- Introduction -- Comparative Institutions -- Political Ideologies -- Public Administration -- International Relations
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Political science; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- General; Political science; Politieke wetenschappen; Science politique